2022
DOI: 10.3390/s22228802
|View full text |Cite
|
Sign up to set email alerts
|

Technological Solutions for Social Isolation Monitoring of the Elderly: A Survey of Selected Projects from Academia and Industry

Abstract: Social isolation is likely to be one of the most serious health outcomes for the elderly due to the COVID-19 pandemic, especially for seniors living alone at home. In fact, two approaches have been used to assess social isolation. The first is a self-reported survey designed for research purposes. The second approach is the use of monitoring technology. The objective of this paper is to provide some illustrative publications, works and examples of the current status and future prospects in the field of monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…These are great directions; however, they are general pointers towards any digital health assessment and intervention platform. The review by Bouaziz et al [ 23 ] is more focused on identifying activities of daily living as indicator of SI. They further provided general recommendations around using different sensors, algorithms and data that can improve such activities to improve detection of SI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are great directions; however, they are general pointers towards any digital health assessment and intervention platform. The review by Bouaziz et al [ 23 ] is more focused on identifying activities of daily living as indicator of SI. They further provided general recommendations around using different sensors, algorithms and data that can improve such activities to improve detection of SI.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has suggested that objective data collected through sensors can help to make inferences regarding SI using predictive modelling [ 23 ]. Previous studies show that time spent napping, length of stay in the living room, amount of physical exercise, and time spent out of the home correlate with self-reported SI [ 1 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, IoT sensors are sensitive to changes in detection environments, such as contact with the target or transitions in temperature and humidity, which may result in inaccurate results [ 12 ]. The most important aspect is that, in cloud computing, where a server-based approach is used, user information is continuously exposed to the server, and if it is hacked, it can lead to severe breaches of personal information [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, the system should not adversely affect the quality of life of elderly people living alone; it should ensure convenience in their daily activities. Fourth, designs that consider data leakage prevention are essential, since monitoring systems deal with sensitive information about the subjects being observed [ 15 ]. Lastly, since the system operates 24/7 and responds to increasing demands, it should have a structure that manages the increase in data without overloading the network, and provides services that operate efficiently with minimal power consumption [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%